Sustainable concrete partially comprised of supplementary cementitious material and alternative fine aggregate- a review - Ab Zail, Nurul Fazilah; Adnan, Suraya Hani (2021)
The waste generation from agricultural and industrial activities contribute to the lack of the landfill disposal area and other environmental imbalance issue. Furthermore, the high consumption of raw materials like sand in the construction sector led to a massive depletion in natural sources to meet the pressure demand in the future. The problem of excessive carbon dioxide (CO2) emissions from cement production activity that led to global warming has initiated this study to find the potential of reducing it. This study reviews the performance of the supplementary cementitious materials (SCM) and the alternative fine aggregates (AFA) from waste products to identify the optimum percentage of waste materials that suitable for the manufacture of sustainable concretes. The reviews enlighten the mechanical properties of the concretes like workability, compressive strength, water absorption, and fire resistance compared to the reference concrete. Quantitative research of the review involves quantifying and analyzing variables obtained from previous studies on the SCM and AFA performances. Despite some concrete properties have significantly reduced after implemented the waste products, the replacement proportions may be controlled at a certain proportion to achieve optimum concrete performance based on the summarized findings in this review. Proper selection of the materials as well as an appropriate treatment like the burning process and pre-treatment procedure could be carried out because it affected the mechanical performances of concrete. Moreover, further study on other durability properties could be the focus for more firm in understanding before implementing the waste products.